Prevalence and Risk Factors of Bovine Fascioliasis in Kelantan, Malaysia: A Cross-Sectional Study - Mohamad Ahmad-Najib; Wan Abdul Wahab Wan-Nor-Amilah; Wong Weng Kin; Muhammad Faez Arizam; Noor Jamil Noor-Izani (Tropical Life Sciences Research, 2021)
Bovine fascioliasis is an important zoonotic parasitic disease that causes significant economic losses to the livestock industry. The aim of this study was to determine the prevalence and risk factors of bovine fascioliasis in Kelantan. In this cross-sectional study, a total of 308 stool and blood samples of farmed cattle were collected from December 2017 to June 2018. The stool samples were examined microscopically for the presence of Fasciola spp. eggs following a formalin-ether sedimentation process. The blood samples were subjected to a commercial ELISA kit (Bio-X-Diagnostic, Rochefort, Belgium) for the detection of anti-Fasciola IgG antibody. The association between coprological findings and risk factors was determined using Pearson’s chi-square (?2). The coproprevalence and seroprevalence of bovine fascioliasis was 14.6% and 37.3%, respectively. There were significant (P < 0.05) associations between the risk of infections and the sex, type of feedings, anthelmintic treatment and farm hygiene. Female cattle (OR: 3.104; 95% CI: 1.265, 7.615), feeding by grazing (OR: 4.458; 95% CI: 1.823, 10.90), untreated cattle (OR: 3.833; 95% CI: 1.620, 9.071), non-schedule anthelminthic treatment (OR: 3.927; 95% CI: 1.685, 9.152) and farm that have never been cleaned (OR: 2.829; 95% CI: 1.428, 5.608) showed higher odds of Fasciola spp. infection. These findings suggested bovine fascioliasis is a serious veterinary disease in Kelantan. Thus, appropriate control, prevention and monitoring strategies of this parasitic infection are urgently needed to reduce the burden of the disease.